Paravalvular leak closure after transcatheter aortic valve replacement with a self-expanding prosthesis - Gafoor, Sameer; Franke, Jennifer (Catheterization and cardiovascular interventions, 2014)
Introduction: Paravalvular leak (PVL) after percutaneous transcatheter aortic valve replacement (TAVR) is associated with significant morbidity and mortality. Percutaneous PVL closure has been reported for balloon-expandable valves but not self-expandable valves. Methods: We conducted a review of cases at our center where patients who received TAVR with self-expandable valves and went on to develop severe PVL underwent percutaneous closure. Baseline demographic, TAVR procedural, PVL procedural, and follow-up data were collected. Results: A total of five patients with severe PVL after TAVR with a self-expanding valve underwent percutaneous PVL closure. Four of five patients had a trial of balloon postdilatation after valve deployment and had significant persistent PVL. In all five patients, PVL went from moderate-severe to mild-moderate PVL. There were no adverse events. Conclusion: Percutaneous PVL closure for severe PVL self-expanding valve for TAVR is a safe and efficacious procedure. Procedural technique involves transesophageal guidance, a high approach through the valve struts, deployment of an appropriate size device, and careful monitoring. This method may be part of the algorithm for severe PVL after TAVR.